Risks and Threats of Social Networks Communication - Pospisil, Jan Zavodny; Zavodna, Lucie Sara (Communications - Scientific letters of the University of Zilina, 2014)
This paper focuses on social networks as a source of information and a tool for its sharing. The first part of the paper defines the theoretical background while the second part is devoted to the evaluation of research which was conducted among university students in the Czech Republic. The main aim of this research is to get a deeper understanding of how students work with information obtained from social networks and to identify the main risks and threats connected with it.